Plant infection by two different viruses induce contrasting changes of vectors fitness and behavior. (30th August 2017) - Chesnais, Quentin; Couty, Aude; Uzest, Maryline; Brault, Véronique; Ameline, Arnaud
Abstract: Insect‐vectored plant viruses can induce changes in plant phenotypes, thus influencing plant–vector interactions in a way that may promote their dispersal according to their mode of transmission (i.e., circulative vs. noncirculative). This indirect vector manipulation requires host–virus–vector coevolution and would thus be effective solely in very specific plant–virus–vector species associations. Some studies suggest this manipulation may depend on multiple factors relative to various intrinsic characteristics of vectors such as transmission efficiency. In anintegrative study, we tested the effects of infection of the Brassicaceae Camelina sativa with the noncirculative Cauliflower mosaic virus (CaMV) or the circulative Turnip yellows virus (TuYV) on the host‐plant colonization of two aphid species differing in their virus transmission efficiency: the polyphagous Myzus persicae, efficient vector of both viruses, and the Brassicaceae specialist Brevicoryne brassicae, poor vector of TuYV and efficient vector of CaMV. Results confirmed the important role of virus mode of transmission as plant‐mediated effects of CaMV on the two aphid species induced negative alterations of feeding behavior (i.e., decreased phloem sap ingestion) and performance that were both conducive for virus fitness by promoting dispersion after a rapid acquisition. In addition, virus transmission efficiency may also play a role in vector manipulation by viruses as only the responses of the efficient vector to plant‐mediated effects of TuYV, that is, enhanced feeding behavior and performances, were favorable to their acquisition and further dispersal. Altogether, this work demonstrated that vector transmission efficiency also has to be considered when studying the mechanisms underlying vector manipulation by viruses. Our results also reinforce the idea that vector manipulation requires coevolution between plant, virus and vector.